Differential expression of long non‐coding RNAs are related to proliferation and histological diversity in follicular lymphomas. (22nd November 2018) - Roisman, Alejandro; Castellano, Giancarlo; Navarro, Alba; Gonzalez‐Farre, Blanca; Pérez‐Galan, Patricia; Esteve‐Codina, Anna; Dabad, Marc; Heath, Simon; Gut, Marta; Bosio, Mattia; Bellot, Pau; Salembier, Philippe; et al.
Summary: Long non‐coding RNAs (lncRNAs) comprise a family of non‐coding transcripts that are emerging as relevant gene expression regulators of different processes, including tumour development. To determine the possible contribution of lncRNA to the pathogenesis of follicular lymphoma (FL) we performed RNA‐sequencing at high depth sequencing in primary FL samples ranging from grade 1‐3A to aggressive grade 3B variants using unpurified ( n  = 16) and purified ( n  = 12) tumour cell suspensions from nodal samples. FL grade 3B had a significantly higher number of differentially expressed lncRNAs (dif‐lncRNAs) with potential target coding genes related to cell cycle regulation. Nine out of the 18 selected dif‐lncRNAs were validated by quantitative real time polymerase chain reaction in an independent series ( n  = 43) of FL. RP4‐694A7.2 was identified as the top deregulated lncRNA potentially involved in cell proliferation. RP4‐694A7.2 silencing in the WSU‐FSCCL FL cell line reduced cell proliferation due to a block in the G1/S phase. The relationship between RP4‐694A7.2 and proliferation was confirmed in primary samples as its expression levels positively related to the Ki‐67 proliferation index. In summary, lncRNAs are differentially expressed across the clinico‐biological spectrum of FL and a subset of them, related to cell cycle, may participate in cell proliferation regulation in these tumours.